Relative income distribution in six European countries: market and disposable income - Petrarca, Ilaria; Ricciuti, Roberto (Luxembourg, 2015)
"The relationship between income inequality and polarization is an empirical fact: a change in equality might occur together with a change in polarization. At the same time, polarization might emerge while inequality remains constant. The outcome of this process entails relevant information about the evolution of the income distribution. We exploit the LIS micro-data to perform a relative distribution analysis for six European countries. Our aim is describing how both the market and the disposable income distributions evolved over time. The results indicate that polarization increased in all the considered countries, being the largest in the United Kingdom and the smallest in Italy. At the beginning of the period the relative polarization of disposable income is lower than the one for market income. In time, however, this pattern is reversed. This evidence does not unambiguously suggest an increasing effectiveness of the equalizing role of the welfare state. Nonetheless, in all the countries downgrading prevails over upgrading: the relevance of the middle-class getting poorer is larger than the one of the middle-class getting richer."